Strategi Koping untuk Permasalahan Harga Diri Rendah dalam Pandangan Islam dan Medis - Subagja, Reva; Kamila, Alda Humaimah; Zalianty, Revalina; Anindia, Sharfina; Nofelinda, Shelfiana; Supriyadi, Tedi; Faozi, Akhmad (Universitas Pahlawan Tuanku Tambusai, 2025)
Low self-esteem is a feeling towards oneself, while problems with poor interpersonal relationships and associated with low anxiety, low affectivity, so that low self-esteem is associated with nursing can cause self-esteem in groups and acceptance of others as valuable in life. High negative self-esteem towards oneself causes loss of self-confidence, pessimism, and is not at risk of depression and schizophrenia, so that negative feelings fundamentally cause loss of self-confidence and self-esteem of individuals and self-esteem disorders (Muhith, 2016). Low Self-Esteem In Islamic teachings, self-esteem (muru'ah) has a very important meaning. Islam teaches its people to maintain self-esteem and dignity, which are considered part of faith. Some key concepts in Islam related to self-esteem include: 'Izzah (Self-Glory): Is a concept that emphasizes the importance of having dignity and honor. In Islam, one must draw closer to Allah to obtain 'izzah, which is a source of glory. Muru'ah: This refers to maintaining self-respect and commendable behavior. Imam Ghazali emphasized that muru'ah is an important attribute in personal transformation, where individuals with high muru'ah will act in accordance with good moral values. 'Iffah (self-restraint): this concept is related to self-control and commendable behavior. Maintaining 'iffah is part of an effort to maintain self-esteem. (Ministry of Religion, 2021) Riskesdas in 2018 stated that 6.7% of the Indonesian population experienced low self-esteem and the highest prevalence was in Yogyakarta with a figure of 10.4%. Research conducted by Aryanyi and Khodijah in 2023 on